Correlations of the physicochemical properties of organosolv lignins from Broussonetia papyrifera with their antioxidant activities. Issue 10 (10th September 2020) - Yao, Lan; Xiong, Long; Yoo, Chang Geun; Dong, Chengyu; Meng, Xianzhi; Dai, Jun; Ragauskas, Arthur J.; Yang, Chunlei; Yu, Jun; Yang, Haitao; Chen, Xiong
Abstract : To understand the influence of lignin characteristics on their antioxidant activities, lignins were isolated from Broussonetia papyrifera by organosolv pretreatment at different temperatures. Abstract : To understand the influence of lignin characteristics on their antioxidant activities, lignins were isolated from Broussonetia papyrifera by organosolv pretreatment at different temperatures. The physicochemical features of the lignins were investigated by GPC, 31 P NMR and 2D HSQC NMR analyses. An increase of organosolv pretreatment temperature resulted in a decrease of M w and an increase of the phenolic hydroxyl group content in the isolated lignin. The lignins extracted at higher organosolv pretreatment temperature showed higher antioxidant activity according to the IC50 determined using DPPH and ABTS. The correlations between the physicochemical properties of organosolv lignins and their antioxidant activities were studied. The contents of phenolic hydroxyl groups, especially syringyl and guaiacyl, and double bonds in the Cα position had positive effects on the antioxidant activity of the lignins. On the other hand, M w and aliphatic hydroxyl groups of the lignins exhibited negative correlations with the antioxidant activity.